PENGARUH FAKTOR UMUR DAN PARITAS TERHADAP KEJADIAN PRE EKLAMPSIA PADA IBU BERSALIN DI RSUD Hj. ANNA LASMANAH BANJARNEGARA TAHUN 2016 - tin Utami (Universitas Harapan Bangsa Purwokerto, 2018)
The causes of preeclampsia and eclampsia have not been known with certainty, but there are several factors that influence the occurrence of preeclampsia in pregnancy, namely primigravida, especially young primigravidas, age> 35 years or <20 years. The purpose of this study was to determine the effect of age and parity on pre eclampsia in mothers. This type of research is correlational analysis through a retrospective approach, with a total sample of 164 cases but there are only 152 cases taken as a whole. The results of this study indicate that age and parity factors influence the incidence of pre-eclampsia with a p value of 0.000 (<0.05). Keywords: Age, Parity, Pre Eclampsia